Capacitive-Discharge-Pumped Copper Bromide Vapor Laser with Output Power Up to 15W; Progress in Electromagnetics Research Symposium (PIERS-Toyama) - Gubarev F. A. Fedor Aleksandrovich (2018, 2018)
Title screen